2016
DOI: 10.1016/j.maturitas.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive aging is associated with changes in oocyte mitochondrial dynamics, function, and mtDNA quantity

Abstract: Mitochondria affect numerous aspects of mammalian reproduction. We investigated whether the decrease in oocyte quality associated with aging is related to altered mitochondria. Oocytes from old (12 months) and young (9 weeks) C57BL/6J mice were compared in relation to: mitochondria morphology and dynamics (mitochondria density, coverage, size and shape) throughout folliculogenesis; levels of mitochondrial DNA (mtDNA); mitochondrial stress reflected in the expression of mitochondrial unfolded protein response (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…The ROS caused by reproductive ageing is associated with changes in oocyte mitochondrial dynamics and function and mtDNA quantity and prevents oocyte maturation40. It has been reported that heat shock results in an inhibitory effect on porcine oocyte maturation in vitro by improving the ROS in the oocytes41.…”
Section: Discussionmentioning
confidence: 99%
“…The ROS caused by reproductive ageing is associated with changes in oocyte mitochondrial dynamics and function and mtDNA quantity and prevents oocyte maturation40. It has been reported that heat shock results in an inhibitory effect on porcine oocyte maturation in vitro by improving the ROS in the oocytes41.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of mitofusion proteins in oocytes negatively affects mitochondrial morphology and dynamics, and is associated with chromosome misalignment when compared to control oocytes (Wakai, Harada, Miyado, & Kono, 2014). Other observations reveal the sensitivity of mitochondrial dynamics to stress and metabolic alterations, and the attendant sensitivity of oocyte developmental potential to mitochondrial regulation (Babayev et al, 2016; Igosheva et al, 2010; Saben et al, 2016). But the changes in oocyte mitochondrial dynamics have long‐term effects as well as immediate effects on the oocyte and early embryo energetics.…”
Section: Mitochondrial Legacymentioning
confidence: 98%
“…In the present study, it was indicated that luteolin induced an increase in ROS level in HT29 cells. Changes in cellular ROS levels are directly associated with changes in mitochondrial function, with abnormalities in the electron permeability of the mitochondrial membrane leading to significant changes in cellular ROS levels (38). Additionally, mitochondria are most vulnerable to ROS attack (39,40).…”
Section: Discussionmentioning
confidence: 99%